When size matters: Biological response to strontium- and cobalt-substituted bioactive glass particles. (2018) - Kargozar, Saeid; Baino, Francesco; Lotfibakhshaiesh, Nasrin; Hill, Robert G.; Milan, Peiman Brouki; Hamzehlou, Sepideh; Joghataei, Mohammad Taghi; Mozafari, Masoud
Abstract: In this study, the biological effects of two different particle sizes of strontium- and cobalt-substituted bioactive glasses (BGs) were compared to reveal the particle size effect. For this aim, the dissolution products of the BG particles with the mean diameter of 9 and 725 µm were added to cell culture media of osteosarcoma cell line SaOS-2. The results of alkaline phosphatase activity assay, alizarin red staining, and real time PCR showed that the smaller particles (9 µm) can be more effective than the larger ones (725 µm) in terms of osteogenesis and angiogenesis. However, 9-micron particles had higher cytotoxicity than the 725-µm samples.